The relationship between objective balance, perceived sense of balance, and fear of falling in stroke patients - ACAR, GÖNÜL; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN; YURDALAN, SAADET UFUK; OĞUZ, SEMRA (TAYLOR & FRANCIS LTD, 2017)
Objective: The objective of our study was to investigate the relationship between objective balance, fear of falling, and perceived sense of balance (PSB) in stroke patients. Methods: Seventy patients aged 18-65 years with chronically developed hemiplegia or hemiparesis were enrolled in the study. Patients' objective balance scores, fear of falling, and PSB were obtained using the berg balance scale (BBS), the falls efficacy scale (FES), and a visual analog scale, respectively. The Standard Mini-Mental Examination was performed to exclude patients with mental disorders from the study. Results: There was a moderate negative correlation between PSB and BBS scores (p = 0.001, rho = -0.588); a strong negative correlation between BBS and FES scores (p = 0.001, rho = -0.808); and a strong positive correlation between PSB and FES scores (p = 0.001, rho = 0.714). We found that BBS scores had negative correlation with PBS scores in left hemiplegic patients while there was no any relationship between BBS and PBS scores in right hemiplegic patients. Conclusion: PSB assessment, besides the BBS, should be considered among the routine assessment methods that enable the rehabilitation team to be aware of patients' balance capacities.
Keywords: Stroke; berg balance scale; perceived sense of balance; fear of falling; VISUAL ANALOG SCALE; QUALITY-OF-LIFE; HEMIPARETIC PATIENTS; POSTURAL BALANCE; PERFORMANCE; PREFERENCE; PAIN